2014
DOI: 10.1176/appi.ajp.2014.14010067
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Metabolism in Major Depressive Disorder

Abstract: Objective Emerging evidence suggests abnormalities in amino acid neurotransmitter function and impaired energy metabolism contribute to the underlying pathophysiology of Major Depressive Disorder (MDD). To test whether impairments in energetics and glutamate neurotransmitter cycling are present in MDD we used in vivo 13C magnetic resonance spectroscopy (13C MRS) to measure these fluxes in individuals diagnosed with MDD relative to non-depressed subjects. Method 1H MRS and 13C MRS data were collected on 23 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 40 publications
5
107
0
6
Order By: Relevance
“…Our search identified 45 studies: 26 studies for the comparison of patients with current MDE versus healthy controls, [8][9][10][11][12][13][14][15][16][17][18]30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] 12 studies for the comparison of patients with current MDE before treatment versus after treatment, 12,20,23,25,26,28,36,43,[47][48][49][50] and 11 for the comparison of euthymic patients and controls. 18,[21][22][23]27,29,38,[51][52][53][54] Figure 1 depicts the study selection proce...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our search identified 45 studies: 26 studies for the comparison of patients with current MDE versus healthy controls, [8][9][10][11][12][13][14][15][16][17][18]30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] 12 studies for the comparison of patients with current MDE before treatment versus after treatment, 12,20,23,25,26,28,36,43,[47][48][49][50] and 11 for the comparison of euthymic patients and controls. 18,[21][22][23]27,29,38,[51][52][53][54] Figure 1 depicts the study selection proce...…”
Section: Resultsmentioning
confidence: 99%
“…For MRS studies, we calculated SMDs for the following regions of interest (ROIs) independently: the occipital cortex, [8][9][10][11][12]14,15,[20][21][22][23][24][25][26][27][28] the anterior cingulate cortex (ACC), 13,15,16,18,22 the dorsolateral prefrontal cortex (dlPFC), 29,30 the ventromedial prefrontal cortex (vmPFC) 29,30 and the left inferior frontal gyrus. 27 We estimated study heterogeneity using the Q statistic when SMDs were significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although speculative in nature, our working hypothesis is that GBCr-under certain circumstances-may reflect overall synaptic strength in a brain region. Considering the tight coupling between synaptic strength, glutamate cycling, and neuroenergetics (Abdallah et al, 2014;Hyder et al, 2013), it is important to highlight that GBCr has been found to positively correlate with rCBF (Liang et al, 2013). Similarly, other GBC-type measures were positively associated with rCBF and cerebral metabolic rate of glucose (Liang et al, 2014;Tomasi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%